Crossborder Care Lessons from Central Europe - Bahna, Miloslav; Sekulová, Martina (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book analyses the circular migration of care workers in Central Europe using the example of Slovak carers in 24-hour care provision for the elderly in Austria. Challenging analyses that focus primarily on care drain and care regimes, Bahna and Sekulová supplement quantitative methodology with qualitative fieldwork to demonstrate the importance of the sending country's economic context. The authors discuss the dynamics of economic differences between Austria and its post-communist neighbors as preconditions of the crossborder care provision, bridging analyses of policy and legal frameworks with approaches from labor migration study. Even as they scrutinize the relevance of care drain-based analyses, Bahna and Sekulová bring to the fore the interplay of economic differences, social policies, gender and migration regimes with geographic proximity to study long-term impacts of care work, including an analysis of employment after care work.